2015
DOI: 10.2147/ibpc.s65632
|View full text |Cite
|
Sign up to set email alerts
|

Renal denervation for the management of resistant hypertension

Abstract: Renal sympathetic denervation (RSD) as a therapy for patients with resistant hypertension has attracted great interest. The majority of studies in this field have demonstrated impressive reductions in blood pressure (BP). However, these trials were not randomized or sham-controlled and hence, the findings may have been overinflated due to trial biases. SYMPLICITY HTN-3 was the first randomized controlled trial to use a blinded sham-control and ambulatory BP monitoring. A surprise to many was that this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 105 publications
0
16
0
Order By: Relevance
“…Resistant hypertension is a medical problem without a clear solution, since antihypertensive medications and renal denervation – the common treatment options to lower blood pressure in these patients – have demonstrated reduced efficacy. 48 , 49 Recently, aerobic exercise training has been recognized as a promising therapeutic tool to reduce blood pressure in resistant hypertension; the blood pressure reduction observed in patients with resistant hypertension following an aerobic exercise training program is promising, but must be confirmed in larger randomized controlled studies.…”
Section: Discussionmentioning
confidence: 99%
“…Resistant hypertension is a medical problem without a clear solution, since antihypertensive medications and renal denervation – the common treatment options to lower blood pressure in these patients – have demonstrated reduced efficacy. 48 , 49 Recently, aerobic exercise training has been recognized as a promising therapeutic tool to reduce blood pressure in resistant hypertension; the blood pressure reduction observed in patients with resistant hypertension following an aerobic exercise training program is promising, but must be confirmed in larger randomized controlled studies.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of experience with RDN in man has been derived in the context of treatment‐resistant hypertension (TRH) using the single‐electrode Symplicity™ catheter (Medtronic, Minneapolis, MN, USA) . The initial first‐in‐man study and open‐label RCT showed the treatment to have profound effects on blood pressure, which in further work were coupled mechanistically to improvements in renal norepinephrine spillover, MSNA and cardiac remodelling .…”
Section: Renal Sympathetic Denervationmentioning
confidence: 99%
“…We then applied a minimum of four ablations to each main renal artery in a circumferential distribution as has been described elsewhere. 6 8 …”
Section: Methodsmentioning
confidence: 99%